Sex and estrogenic effects on coexpression of mRNAs in single ventromedial hypothalamic neurons - Devidze, N. (National Academy of Sciences, 2005)
Regulated gene expression in single neurons can be linked to biophysical events and behavior in the case of estrogen-regulated gene expression in neurons in the ventrolateral portion of the ventromedial nucleus (VMN) of the hypothalamus. These cells are essential for lordosis behavior. What genes are coexpressed in neurons that have high levels of mRNAs for estrogen receptors (ERs)? We have been able to isolate and measure certain mRNAs from individual VMN neurons collected from rat hypothalamus. Large numbers of neurons express mRNA for ERα, but these neurons are not identical with the population of VMN neurons expressing the likely gene duplication product, ERβ. An extremely high proportion of neurons expressing either ER also coexpress mRNA for the oxytocin receptor (OTR). This fact matches the known participation of oxytocin binding and signaling in sexual and affiliative behaviors. In view of data that ER and OTR can signal through PKCs, we looked at coexpression of selected PKCs in the same individual neurons. The most discriminating analysis was for triple coexpression of ERs, OTR, and each selected PKC isoform. These patterns of triple coexpression were significantly different for male vs. female VMN neurons. Further, individual neurons expressing ERα could distribute their signaling across the various PKC isoforms differently in different cells, whereas the reverse was not true. These findings and this methodology establish the basis for systematic linkage of the brain's hormone-sensitive signaling pathways to biophysical and behavioral mechanisms in a well studied mammalian system.